2015
DOI: 10.1134/s1021443715030206
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll content, leaf gas exchange and growth of oriental lily as affected by shading

Abstract: We evaluated the effects of light conditions on leaf gas exchange, chlorophyll content, and growth responses in the Oriental lily (Lilium auratum L.) cv. Sorbonne. The experiment involved application on increasing shade densities (0, 60, 75, and 80%) to Sorbonne, and was carried out in the Horqin Sandy Land of northern China. Shade tests showed that growth of the lily was primarily affected by the level of irradiance. Photoinhibition occurred in the 0 and 60% shade treatments, but not in the 75 and 80% shade t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The plant began to wither gradually during the half-withered stage, and the fresh weight of stems and leaves also began to decline. Chlorophyll, as the absorption, transfer and transformation of light energy in photosynthesis, plays a key role in plant photosynthesis and is one of the important indexes reflecting plant photosynthesis [ 32 ]. The chlorophyll content began to decrease sharply after flowering ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The plant began to wither gradually during the half-withered stage, and the fresh weight of stems and leaves also began to decline. Chlorophyll, as the absorption, transfer and transformation of light energy in photosynthesis, plays a key role in plant photosynthesis and is one of the important indexes reflecting plant photosynthesis [ 32 ]. The chlorophyll content began to decrease sharply after flowering ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2017) and Zhang et al (1995) reported that chlorophyll b per unit leaf area was significantly higher in shaded plants than in unshaded plants as a result of extensive stacking of grana (Cooper & Qualls, 1967), which, in turn, lead to a larger antenna for photosystem II and therefore more light being harvested in shaded plants. Zhang et al (2015) and Wittmann et al (2001) also reported that chlorophyll content of leaves was significantly affected by shading. Under shade, light absorption is optimized by increasing the density of chlorophyll pigments per unit leaf area.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 91%
“…Chlorophylls (Chl) are the magnesium-containing tetrapyrroles necessary for light capturing and energy transmission in plants (Ohmiya et al 2014). In shade conditions, Lilium auratum absorbs light energy by synthesizing large amounts of Chl and increasing net photosynthesis, which can assure plant development, however, the influence of light intensity and waterlogging stress on Chl content has no consistent conclusion (Zhang et al 2015). The Chl concentration of Zea mays was reduced as shade increased, limiting photosynthetic and organic synthesis (Chen et al 2013).…”
Section: The Consequences Of Waterlogging In Plantsmentioning
confidence: 99%